Absolute monotonicity of a function involving the exponential function - Qi, Feng (Global Journal of Mathematical Analysis, 2014)
In the paper, the author verifies the absolute monotonicity of a function involving the exponential function. Keywords: absolute monotonicity; absolutely monotonic function; completely monotonic function; completely monotonic degree; exponential function MSC: Primary 26A48; Secondary 33B10, 44A10